The specificity of S1 nuclease toward RNA-DNA hybrids as studied using isotopes of phosphorus-32 and phosphorus-33. - Wittelsberger, S C (1977)
Hybrids were formed from Bacillus cereus DNA and ribosomal RNA. They were treated with various combination of S1 nuclease and ribonuclease, and the molar ratios of the RNA and DNA moieties remaining in the treated hybrids were determined using a 32P-33P dual-label technique. It was found that both S1 nuclease and ribonuclease are required to give hybrid with RNA and DNA in a perfect 1:1 molar ratio. It was noted that the dual-label technique which employs orthophosphate as the sole phosphorus source for both labels gives unambiguous molar ratios and obviates the need to calculate specific activities, make quench corrections, or correct for base content.